Effect of Monosodium Glutamate on In vitro Oocyte Maturation and Embryonic Development after Parthenogenesis in Pigs - Minji Kim; Hyeji Shin; Joohyeong Lee; Seung Tae Lee; Eunsong Lee (The Korean Society of Animal Reproduction and Biotechnology, 2017)
This study was designed to determine the effect of monosodium glutamate (MSG) on in vitro maturation (IVM) of oocytes and early development of parthenogenesis (PA) embryos in pigs. Each IVM and IVC medium was supplemented with various concentrations (0, 0.1, 0.5 and 5 mM) of MSG and non-essential amino acids (NEAA) depending on the experimental design. Immature pig oocytes were matured for 44 h and then oocytes reached metaphase II (MII) stage were electrically activated to induce parthenogenesis (PA). When immature oocytes were treated with MSG in the absence of NEAA during IVM, nuclear maturation (83.1-87.1%), intra-oocyte glutathione content, cumulus expansion, and cleavage (91.4-93.4%) of PA embryos were not influenced by MSG treatment at all concentrations. However, blastocyst formation of PA embryos was significantly increased by 5.0 mM MSG (45.3 ± 6.2%) compared to control (25.6 ± 3.4%). MSG treatment during IVM in the presence of NEAA did not show significant effect on nuclear maturation of oocytes and blastocyst formation after PA while 0.5 mM MSG (89.3 ± 1.9%) decreased (P < 0.05) cleavage of PA embryos compared to 0.1 mM MSG (94.6 ± 1.1%). When PA embryos were treated for 7 days with MSG during IVC, 5.0 mM MSG significantly decreased blastocyst formation (27.8 ± 4.9%) compared to no treatment (41.4 ± 1.9%) while no decrease in blastocyst formation was observed in 0.1 and 0.5 mM (37.4 ± 3.4% and 34.4 ± 2.6%, respectively). Our results demonstrated that 5 mM MSG in a NEAA-free chemically defined maturation medium showed positive effect on PA embryonic development while 5 mM MSG treatment during IVC was deleterious to PA embryonic development in pigs.